2021
DOI: 10.1002/hpm.3323
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 pandemic responses of Canada and United States in first 6 months: A comparative analysis

Abstract: Introduction Canada and the United States have distinct health care and social policies, and it is important to see how they had been responding to the ongoing COVID‐19 pandemic. Methods The study period was limited to the first 6 months of the pandemic and aimed to explore the responses by public health authorities, media, general population, and law makers during the initial phase of pandemic. Results Social disparity, underfunded pandemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 30 publications
(45 reference statements)
0
24
0
1
Order By: Relevance
“…Previous research has also shown that pandemics can have a significant psychological, physical, and emotional impact on nurses [ 5 , 8 , 10 , 12 , 23 , 24 ]. As Fernandez notes, research from both the ongoing COVID-19 pandemic and previous pandemics demonstrate the need to develop policies that support the emotional, mental and physical well-being of nurses working on the frontlines during these emergencies [ 5 ].Psychological support, received during and after a pandemic, can be a key factor in reducing these feelings of burnout among nurses [ 23 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has also shown that pandemics can have a significant psychological, physical, and emotional impact on nurses [ 5 , 8 , 10 , 12 , 23 , 24 ]. As Fernandez notes, research from both the ongoing COVID-19 pandemic and previous pandemics demonstrate the need to develop policies that support the emotional, mental and physical well-being of nurses working on the frontlines during these emergencies [ 5 ].Psychological support, received during and after a pandemic, can be a key factor in reducing these feelings of burnout among nurses [ 23 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Again, despite these findings, the Canadian response to COVID-19 indicates that these lessons from previous outbreaks were not fully considered [ 5 , 8 , 9 ], with gaps in implementation evident during the current pandemic. Additionally, research to inform interventions to better support front-line nurses, and critical care nurses in particular, during a prolonged pandemic are lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though it is very clear that the COVID pandemic has exposed the long-standing fault lines in our social and health systems ( Combden et al, 2022 ; Salerno et al, 2020 ), it has also forced us to recognize our shared inter-connectedness across classes, colours, and creeds through our shared humanity and shared vulnerability. As occupational therapy student Deanna Toews reminded me during a recent class discussion, “we are all earthlings” (personal communication, May 8, 2021).…”
Section: Reflectionsmentioning
confidence: 99%
“…S’il est très clair que la pandémie de COVID a mis en évidence les failles de longue date de nos systèmes sociaux et de santé ( Combden et al, 2022 ; Salerno et al, 2020 ), celle-ci nous a aussi forcés à reconnaître notre interdépendance au-delà des classes, des couleurs et des croyances, à travers notre humanité et notre vulnérabilité communes. Comme l’étudiante en ergothérapie Deanna Toews me l’a rappelé lors d’une récente discussion en classe, « nous sommes tous des terriens » (communication personnelle, 8 mai 2021).…”
Section: Réflexionsunclassified